2015
DOI: 10.1111/1758-2229.12343
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on microbial dark matter: a TM6 bacterium as natural endosymbiont of a free‐living amoeba

Abstract: The TM6 phylum belongs to the so-called microbial dark matter that gathers uncultivated bacteria detected only via DNA sequencing. Recently, the genome sequence of a TM6 bacterium (TM6SC1) has led to suggest that this bacterium would adopt an endosymbiotic life. In the present paper, free-living amoebae bearing a TM6 strain were isolated from a water network. The amoebae were identified as Vermamoeba vermiformis and the presence of a TM6 strain was detected by polymerase chain reaction and microscopy. The part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 44 publications
7
31
0
Order By: Relevance
“…nov.) is proposed. This family also contains the original MAG of JCVI_TM6SC1 and might also harbour Vermiphilus pyriformis, based on a partial 16S sequence [5]. The basal nodes in the 16S rDNA ML tree are poorly supported, likely due to undersampling, and similar to previous analysis ( Figure 8A) [4].…”
Section: Tm6/dependentiaesupporting
confidence: 79%
See 2 more Smart Citations
“…nov.) is proposed. This family also contains the original MAG of JCVI_TM6SC1 and might also harbour Vermiphilus pyriformis, based on a partial 16S sequence [5]. The basal nodes in the 16S rDNA ML tree are poorly supported, likely due to undersampling, and similar to previous analysis ( Figure 8A) [4].…”
Section: Tm6/dependentiaesupporting
confidence: 79%
“…The genomic complement, enriched in conserved gene functions found in endosymbionts or parasites of eukaryotes such as Chlamydia, Wolbachia, and Rickettsia, further suggested that TM6 was associated with eukaryotic hosts [3,4]. Indeed, two representatives of the TM6 phylum were since isolated in amoebae, competent hosts to a vast array of bacterial, eukaryotic, and viral symbionts and pathogens [5,6]. The first isolate, Babela massiliensis, is an obligate pathogen that causes lysis of its host, Acanthamoeba castellanii, while the other, Vermiphilus pyriformis, maintains a stable relationship with its host Vermamoeba vermiformis, suggesting that different TM6 bacteria might employ different life history strategies [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of symbionts per amoeba cell varied and ranged from a few to over 100. The infection did not compromise the host’s capability to encyst as described for some other symbionts 16, 42 , nor did we observe pronounced lysis of the amoeba at room temperature or at 28 °C. Over a period of two years, the amoebae remained infected, demonstrating that this symbiont-amoeba relationship is a stable long-term association.…”
Section: Resultssupporting
confidence: 69%
“…This first isolated geothermal nanoarchaeon, proposed as "Candidatus Nanopusillus acidilobi" represents the smallest cultured organism to date (100-300 nm cell size), and available cultures now allow experimentation to reveal its particular metabolism and adaptation features. Many more ultra-small bacteria and archaea with similar ectosymbiotic or ectoparasitic lifestyles might await discovery and identification of their hosts, something that -apart from single cell genomics -is only feasible by direct cultivation (Delafont et al 2015;He et al 2015;Wurch et al 2016). We conclude that genomic information of microbes derived from low diversity environments can often be obtained relatively easily and that individual genome reconstructions are often feasible (Figure 3).…”
Section: Extreme Environmentsmentioning
confidence: 91%